Wrażliwość i miłosierdzie fundamentem i drogą świętości - SZOSTEK, Andrzej (Ethos. Kwartalnik Instytutu Jana Pawła II KUL, 2014)
The starting point of the present refl ections is the Biblical image of the Last Judgment. The severe sentence for those who did not feed the hungry or did not visit the sick is explained by the fact that the judgment in question is one of the heart rather than administering punishment for the offences. Indifference to the fate of another human being depraves the human heart and contributes to the image of God that has nothing in common with the God of Jesus Christ. If holiness means above all living in Christ (rather than an egoistic pursuit of one’s own perfection), the path towards holiness starts, importantly, with being sensitive to the poverty and problems of the ‘least brothers’ and with readiness to provide charitable help for them. The author refers to the fi gures of saints (e.g. the Blessed Teresa of Calcutta and St. Br. Albert) as well as to uncanonized heroes of charity (e.g. Mahatma Gandhi, Albert Schweitzer, and Otto Schi-mek), and observes that the transformation of their lives was not triggered bya struggle against sin or a desire to pursue virtues, but rather by their ‘weakness’ expressed in incapability of coming to terms with the poverty affecting others. In conclusion the author refers to the teaching of the recent Popes, in particular to the teaching of John Paul II, who was determined to show God rich in charity and who appealed for a new ‘creativity’ in charity.